Penerapan Prinsip Teknik Industri dalam Meningkatkan Efisiensi Manajemen Pendidikan di Perguruan Tinggi - Haviana, Evan (Penerbit Widina, Widina Media Utama, 2025)
This study aims to analyze the effectiveness of educational management in higher education institutions using an industrial engineering approach. The research focuses on evaluating administrative workflows, faculty workload distribution, the quality of academic services, and resource utilization efficiency. Methods employed include in-depth interviews, observation, documentation, Focus Group Discussions (FGD), as well as analyses based on work study, lean management, quality function deployment (QFD), and system simulation. The results indicate the presence of non-value-added administrative activities, uneven workload distribution, and suboptimal inter-unit communication. System simulations and the application of industrial engineering principles demonstrate a potential efficiency improvement of up to 30%, enhanced service quality, and increased satisfaction among students and staff. This study emphasizes the importance of integrating industrial engineering principles into educational management to create a more efficient, adaptive, and sustainable system.ABSTRAKPenelitian ini bertujuan untuk menganalisis efektivitas manajemen pendidikan di institusi pendidikan tinggi dengan menggunakan pendekatan teknik industri. Fokus penelitian meliputi evaluasi alur kerja administrasi, distribusi beban kerja dosen, kualitas layanan akademik, dan efisiensi pemanfaatan sumber daya. Metode yang digunakan meliputi wawancara mendalam, observasi, dokumentasi, Focus Group Discussion (FGD), serta analisis berbasis work study, lean management, quality function deployment (QFD), dan simulasi sistem. Hasil penelitian menunjukkan adanya aktivitas administrasi yang tidak bernilai tambah, distribusi beban kerja yang tidak merata, dan komunikasi antarunit yang kurang optimal. Simulasi sistem dan penerapan prinsip teknik industri memperlihatkan potensi peningkatan efisiensi hingga 30%, perbaikan kualitas layanan, serta peningkatan kepuasan mahasiswa dan staf. Penelitian ini menegaskan pentingnya integrasi prinsip teknik industri dalam manajemen pendidikan untuk menciptakan sistem yang lebih efisien, adaptif, dan berkelanjutan